An approach for effective stakeholder engagement as an essential component of the ecosystem approach. (2nd February 2017) - Oates, Jennifer; Dodds, Lyndsey A.
Abstract : Effective stakeholder engagement is an essential, but commonly overlooked, component of the ecosystem approach. In this article, we draw lessons from two European Union LIFE+ (LIFE is the European Union's financial instrument supporting environmental, nature conservation and climate action projects throughout the EU.) funded projects led by WWF-UK: PISCES (Partnerships Involving Stakeholders in the Celtic sea EcoSystem) and the Celtic Seas Partnership to present an approach for effective stakeholder engagement. These projects developed steps to operationalise the ecosystem approach within the context of a key piece of European legislation: the Marine Strategy Framework Directive (MSFD, 2008/56/EC). We identified an approach for involving stakeholders in delivery of the ecosystem approach, which can be applied to other areas and contexts. The approach involves four steps: Identify a relevant policy framework and the role of stakeholders in its implementation and identify or agree environmental, social and economic objectives for the area. Create an open, neutral, cross-sectoral forum and design an engagement process that creates a "safe" and inclusive space, and is facilitated independently. Demystify terminology and develop a shared vision or principles through an engagement process Collaboratively develop management actions that are needed to achieve objectives and implement them.